Sodium-ion battery positive electrode slurry composition and preparation method and application thereof

By optimizing the ratio of the positive electrode slurry composition of sodium ion battery, improving the active substance content and electrochemical contact of sodium nickel manganate, the problems of low energy density and poor cycle stability of existing sodium ion batteries have been solved, and the further development of the High electrochemical properties and lower production costs.

CN119517965AInactive Publication Date: 2025-02-25CHINA SODA ENERGY (YANGZHOU) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411737461.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode slurry compositions have insufficient active substance content and unreasonable proportion of conductive agent addition, resulting in low energy density and poor circulation stability, which limits the application of sodium ion batteries.

Method used

Sodium nickel manganate is used as the positive electrode material to control its particle size and purity, and by optimizing the ratio of conductive agents, binders and sodium nickel manganate, the content of active substances and electrochemical contact are improved, thereby improving the energy density and cycle stability of sodium ion batteries.

Benefits of technology

It improves the charge and discharge performance, rate performance and cycle stability of sodium ion batteries, broadens its application areas, and reduces production costs, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the field of sodium-ion batteries, and particularly discloses a sodium-ion battery positive electrode slurry composition as well as a preparation method and application thereof. Raw materials used by the sodium ion battery positive electrode slurry composition comprise the following components: 100 parts by weight of sodium nickel manganese oxide, 1.5-2.5 parts by weight of a conductive agent and 6-8 parts by weight of a binder, wherein the binder comprises sodium carboxymethyl cellulose and polyvinylidene fluoride in a weight ratio of (1.8-2.2): 1; the particle size D50 of the sodium nickel manganese oxide is 6-10 [mu] m, and the purity of the sodium nickel manganese oxide is greater than 99.5%. According to the positive electrode slurry composition disclosed by the invention, the sodium-ion battery can have good charge-discharge performance, rate capability and cycling stability, the application field of the sodium-ion battery is widened, and the positive electrode slurry composition particularly has excellent performance in occasions of long-time operation and frequent charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and more specifically, to a sodium ion battery positive electrode slurry composition and a preparation method and application thereof. Background Art

[0003] The existing applicable energy systems include solar energy, wind energy, hydropower, tidal energy, etc. The utilization of these energy sources usually needs to be converted into electrical energy. However, these energy sources are limited by factors such as region, climate, and season, and it is difficult to ensure sustainability. Therefore, electrochemical energy storage devices have become a key link in the new energy system. In addition to playing a key role in the conversion of natural energy, electrochemical energy storage devices also have important applications in other areas, such as backup power supplies, electric tricycles, and electric vehicles. At present, lithium-ion batteries dominate electrochemical energy storage devices. With the rapid development of the new energy industry and the scarcity of lithium resources, the price of lithium salts used in lithium-ion batteries has fluctuated greatly, and the cost of batteries has also fluctuated, which has had a significant impact on the entire new energy industry. In addition, the performance of lithium-ion batteries themselves also has shortcomings, and low-temperature discharge performance, rate charging performance, and safety performance need to be further improved.

[0004] Sodium, a member of the same family as lithium, is rich in resources and low in cost. The research and development of sodium-ion batteries can, to a certain extent, alleviate the problem of limited battery development caused by the shortage of lithium resources, and have greater market competitive advantages than lithium-ion batteries in some application fields. Sodium-ion batteries are mainly composed of positive electrode slurry compositions, negative electrode materials, diaphragms, electrolytes, aluminum-plastic casings, etc., among which the positive electrode slurry composition is one of the key factors determining the performance and application of sodium-ion batteries. However, the existing positive electrode slurry compositions of sodium-ion batteries generally have problems such as insufficient active material content and unreasonable proportions of conductive additives, which make the energy density of the prepared sodium-ion batteries low and the cycle stability poor, which greatly limits the application of sodium-ion batteries. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a sodium ion battery positive electrode slurry composition and a preparation method and application thereof.

[0006] In the first aspect, the present application provides a sodium ion battery positive electrode slurry composition, which adopts the following technical solution: A sodium ion battery positive electrode slurry composition, the raw materials used include the following components: 100 parts by weight of sodium nickel manganate; Conductive agent 1.5-2.5 parts by weight; 6-8 parts by weight of binder; The binder comprises sodium carboxymethyl cellulose and polyvinylidene fluoride in a weight ratio of (1.8-2.2):1; The particle size D50 of the sodium nickel manganate is 6-10 μm, and the purity is greater than 99.5%.

[0007] By adopting the above technical scheme, the present application selects sodium nickel manganate, a transition metal layered oxide, as the positive electrode material, and controls its particle size, thereby increasing the compaction density of the positive electrode material, thereby increasing the content of active substances per unit volume. And by controlling the ratio between the conductive agent, the binder and sodium nickel manganate, the content of active substances in the positive electrode slurry composition is increased, and good electrochemical contact is maintained, thereby improving the energy density and cycle stability of the positive electrode of the sodium ion battery. At the same time, the present application also uses sodium carboxymethyl cellulose and polyvinylidene fluoride mixed in a certain ratio as a binder, which helps the positive electrode slurry composition to form a stable bonding structure, thereby increasing the cycle life of the sodium ion battery.

[0008] Preferably, the amount of the conductive agent is 2 parts by weight.

[0009] Through the above technical solution, the present application further controls the amount of the conductive agent to 2% by weight of the sodium nickel manganese oxide, which can further improve the energy density and cycle stability of the positive electrode slurry composition, thereby further improving the electrochemical performance of the sodium ion battery.

[0010] Preferably, the weight ratio of sodium carboxymethyl cellulose to polyvinylidene fluoride is 2:1.

[0011] By adopting the above technical solution, the present application further controls the weight ratio of sodium carboxymethyl cellulose and polyvinylidene fluoride to 2:1, which can further optimize the stability of the bonding structure of the positive electrode slurry composition, thereby further enhancing the cycle life of the sodium ion battery.

[0012] Preferably, the sodium nickel manganate is P6 phase sodium nickel manganate. Further, the P6 phase sodium nickel manganate is synthesized by a high temperature solid phase sintering method, specifically: firstly, Ni(C2H3O2)2·4H2O and Mn(C2H3O2)2·4H2O are dissolved in water and then freeze-dried to obtain a uniformly mixed acetate, and then pre-sintered in a muffle furnace to form a transition metal oxide precursor, and then the obtained precursor and sodium iodide are mixed uniformly by grinding, and finally further high temperature solid phase sintering is performed to obtain P6 phase sodium nickel manganate.

[0013] Through the above technical solution, compared with P3 phase sodium nickel manganate, the interaction between Ni and O between the transition metal layer in the P6 phase sodium nickel manganate of the present application is stronger. 2+ It is more difficult to fall out and not easy to be combined with H + Replacement occurs, which is more conducive to the diffusion of sodium ions, and can significantly improve the charge and discharge performance, rate performance and electrochemical cycle stability of sodium ion batteries.

[0014] Preferably, the conductive agent comprises graphene and carbon nanotubes in a weight ratio of 1:(2-3).

[0015] Preferably, the weight ratio of the graphene to the carbon nanotubes is 1:3.

[0016] Through the above technical scheme, the present application mixes and matches graphene and carbon nanotubes, and utilizes the complementary structural properties of the two under the action of synergistic effect, giving full play to their respective advantages, so that the conductive agent has better conductivity than a single material, and further improves the electrochemical performance of the sodium ion battery. In addition, the present application optimizes the ratio between the two, so that the conductive agent can better form a point-line-surface three-dimensional conductive structure, thereby obtaining better conductive performance. Experimental data show that when the weight ratio of graphene and carbon nanotubes is 1:3, the final sodium ion battery can have better electrochemical performance.

[0017] Preferably, the carbon nanotubes are single-walled carbon nanotubes.

[0018] Through the above technical solution, compared with multi-walled carbon nanotubes, the single-walled carbon nanotubes of the present application have fewer tube walls, a higher aspect ratio and fewer defects, and present a highly graphitized structure, which is conducive to electron transition, improves the conductivity of the conductive agent, and enables the sodium ion battery to exhibit better electrochemical performance.

[0019] Preferably, the single-walled carbon nanotubes are prepared by the following method: At a temperature of 1000-1050° C. and under the protection of an inert gas, hydrogen and methane are simultaneously introduced into a system containing a catalyst for reaction for 25-35 minutes, and then cooled to room temperature to obtain single-walled carbon nanotubes.

[0020] Through the above technical solution, the present application optimizes the temperature during the preparation of single-walled carbon nanotubes, so that the prepared single-walled carbon nanotubes have fewer defects and a higher degree of graphitization, and when applied to sodium ion batteries, the sodium ion batteries exhibit better electrochemical performance. In addition, the present application simultaneously introduces hydrogen and methane into the system, which can reduce the Fe element to Fe particles while promoting the combination of C elements in the catalytic cracking process of methane. If they are not introduced at the same time, the Fe element will be completely reduced, thereby forming a large-sized metal particle aggregate, which affects the conductivity of the single-walled carbon nanotubes.

[0021] Furthermore, the catalyst is a Fe-Mo / MgO catalyst, and the Mo in the catalyst can also effectively inhibit the agglomeration of the Fe element, which is helpful for the subsequent regulation of the growth of single-walled carbon nanotubes.

[0022] Furthermore, the Fe-Mo / MgO catalyst is prepared by the following method: Fe(NO3)3·9H2O and (NH4)6Mo7·4H2O were dissolved in water and then added dropwise to MgO powder until an orange-yellow slurry appeared. The slurry was then freeze-dried and calcined to obtain a Fe-Mo / MgO catalyst.

[0023] In a second aspect, the present application provides a method for preparing a sodium ion battery positive electrode slurry composition, which adopts the following technical solution: A method for preparing a sodium ion battery positive electrode slurry composition comprises the following steps: The sodium nickel manganese oxide, the conductive agent and the binder are mixed evenly, then dispersed in N-methylpyrrolidone, and wet ball milled to obtain a positive electrode slurry composition for a sodium ion battery.

[0024] In a third aspect, the present application provides an application of a sodium ion battery positive electrode slurry composition, which adopts the following technical solution: An application of a sodium ion battery positive electrode slurry composition, wherein the sodium ion battery positive electrode slurry composition is coated on a substrate, and then dried, solidified and compacted to obtain a positive electrode sheet.

[0025] Furthermore, the substrate is a metal aluminum foil, the specification of the metal aluminum foil is (12±2) μm×528 mm, and the reference surface density is 3.4 mg / cm 2 The coating process adopts spin coating to enhance the uniformity of coating the positive electrode slurry composition on the metal aluminum foil, thereby improving the electrochemical performance of the sodium ion battery.

[0026] Furthermore, the single-sided surface density of the positive electrode sheet is 9.75±0.1 mg / cm 2 , double-sided surface density is 19.50±0.2mg / cm 2 .

[0027] In summary, this application has the following beneficial technical effects: 1. The positive electrode slurry composition of the present application can enable the sodium ion battery to have good charge and discharge performance, rate performance and cycle stability, broaden the application field of sodium ion batteries, especially perform well in long-term operation and frequent charging situations; 2. The positive electrode slurry composition of the present application adopts economical and efficient materials and processing technology, reduces the production cost of sodium ion batteries, and is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] Unless otherwise specified, the raw materials used in this application are all commercially available products commonly used in the field.

[0030] Preparation Example 1 The preparation method of P6 phase sodium nickel manganate comprises the following steps: a. First, Ni(C2H3O2)2·4H2O and Mn(C2H3O2)2·4H2O were dissolved in deionized water at a molar ratio of Ni to Mn of 1:1, and then frozen and solidified into a solid and then freeze-dried for 24 hours to obtain a mixed powder; b. The mixed powder is heated to 400°C at a heating rate of 4°C / min and pre-sintered for 3 hours, then ground and mixed evenly with NaI, wherein the molar ratio of Na to Ni is 7:5, then heated to 500°C at a heating rate of 5°C / min and kept warm for 3 hours, then heated to 800°C at a heating rate of 1°C / min and kept warm for 10 hours, finally obtaining P6 phase sodium nickel manganate with a particle size D50 of 6-10μm and a purity greater than 99.5%.

[0031] Preparation Example 2 The preparation method of P3 phase sodium nickel manganate comprises the following steps: a. First, NaC2H3O2, Ni(C2H3O2)2·4H2O and Mn(C2H3O2)2·4H2O are dissolved in deionized water according to the molar ratio of Na, Ni and Mn of 1.4:1:1, and then the mixture is frozen and solidified into a solid and then freeze-dried for 24 hours to obtain a mixed powder; b. The mixed powder is heated to 400°C at a heating rate of 4°C / min and pre-sintered for 3 hours, and then after grinding, the mixture is heated to 500°C at a heating rate of 5°C / min and kept warm for 3 hours, and then heated to 800°C at a heating rate of 1°C / min and kept warm for 10 hours, and finally a P3 phase sodium nickel manganate with a particle size D50 of 6-10μm and a purity greater than 99.5% is obtained.

[0032] Preparation Example 3 The method for preparing single-walled carbon nanotubes comprises the following steps: The Fe-Mo / MgO catalyst was placed in a tubular furnace and Ar was introduced at a flow rate of 500 sccm. The tubular furnace was then heated to 1000°C at a heating rate of 5°C / min. Hydrogen and methane were then introduced simultaneously at flow rates of 400 sccm and 70 sccm, respectively, for 25 minutes. The mixture was then cooled to room temperature to obtain single-walled carbon nanotubes with a diameter of 2.89-5.07 nm and a length of 1-5 μm.

[0033] The Fe-Mo / MgO catalyst was prepared by the following method: (Fe(NO3)3·9H2O and (NH4)6Mo7·4H2O were dissolved in water and then added dropwise to the MgO powder until an orange-yellow slurry was present, the weight ratio of MgO powder, Fe(NO3)3·9H2O and (NH4)6Mo7·4H2O was 10:1.5:1, and then the slurry was frozen at -18°C for 12h, then freeze-dried at a pressure of 5MPa for 48h, and then calcined at 800°C for 2h to obtain the Fe-Mo / MgO catalyst.

[0034] Preparation Example 4 The method for preparing single-walled carbon nanotubes comprises the following steps: The Fe-Mo / MgO catalyst was placed in a tube furnace, and Ar was introduced at a flow rate of 500 sccm, then the tube furnace was heated to 1050°C at a heating rate of 5°C / min, and hydrogen and methane were introduced at flow rates of 400 sccm and 70 sccm respectively for 35 minutes, and then cooled to room temperature to obtain single-walled carbon nanotubes with a diameter of 2.89-5.07 nm and a length of 1-5 μm; wherein the Fe-Mo / MgO catalyst was prepared by the following method: Fe( NO3)3·9H2O and (NH4)6Mo7·4H2O were dissolved in water and then added dropwise to MgO powder until an orange-yellow slurry was obtained. The weight ratio of MgO powder, (Fe(NO3)3·9H2O and (NH4)6Mo7·4H2O was 10:1.5:1. The slurry was then frozen at -18°C for 12 h, freeze-dried at 5 MPa for 48 h, and calcined at 800°C for 2 h to obtain a Fe-Mo / MgO catalyst.

[0035] Preparation Example 5 The difference from Preparation Example 3 is that the tube furnace is heated to 1100° C. at a heating rate of 5° C. / min, and the rest is the same as Preparation Example 3.

[0036] Preparation Example 6 The difference from Preparation Example 3 is that the tube furnace is heated to 1150° C. at a heating rate of 5° C. / min, and the rest is the same as Preparation Example 3.

[0037] Preparation Example 7 The difference from Preparation Example 3 is that hydrogen is first introduced at a flow rate of 400 sccm to react for 10 minutes, and then methane is introduced at a flow rate of 70 sccm to react for 15 minutes. The rest is the same as Preparation Example 3.

[0038] Preparation Example 8 The method for preparing multi-walled carbon nanotubes comprises the following steps: The Fe-Al2O3 catalyst was placed in a tube furnace, and Ar was introduced at a flow rate of 500 sccm, then the tube furnace was heated to 800°C at a heating rate of 5°C / min, hydrogen was introduced at a flow rate of 500 sccm for 20 min, the flow rate was adjusted to 100 sccm, propane was introduced at a flow rate of 300 sccm for 120 min, and then cooled to room temperature to obtain multi-walled carbon nanotubes with a diameter of 33.07-37.04 nm and a length of 5 μm; Among them, the Fe-Al2O3 catalyst was prepared by the following method: Fe(NO3)3·9H2O, Al(NO3)3·9H2O and citric acid monohydrate in a weight ratio of 20.2:18.76:21.01 were added to water and mixed and stirred until no particles were present, then heated to 100°C in an oil bath and kept warm for 8 hours, then dried at 120°C for 12 hours and ground, then heated to 200°C at a heating rate of 5°C / min and kept warm for 120 minutes, then heated to 800°C at a heating rate of 5°C / min and kept warm for 60 minutes, finally cooled to room temperature and ground through a 300-mesh sieve to obtain the Fe-Al2O3 catalyst.

[0039] Example 1 A method for preparing a sodium ion battery positive electrode slurry composition comprises the following steps: 100 g of sodium nickel manganese oxide, 1.5 g of a conductive agent and 8 g of a binder were uniformly mixed, and then dispersed in N-methylpyrrolidone, and wet-milled and mixed into a slurry to obtain a sodium ion battery positive electrode slurry composition; Wherein, the sodium nickel manganese oxide is the sodium nickel manganese oxide prepared in Preparation Example 1; The binder includes sodium carboxymethyl cellulose and polyvinylidene fluoride in a weight ratio of 1.8:1, wherein the sodium carboxymethyl cellulose is 5.14 g and the polyvinylidene fluoride is 2.86 g; The conductive agent is graphene.

[0040] Example 2 A method for preparing a sodium ion battery positive electrode slurry composition comprises the following steps: 100 g of sodium nickel manganese oxide, 2.5 g of a conductive agent and 6 g of a binder were uniformly mixed, and then dispersed in N-methylpyrrolidone, and wet-milled and mixed into a slurry to obtain a sodium ion battery positive electrode slurry composition; Wherein, the sodium nickel manganese oxide is the sodium nickel manganese oxide prepared in Preparation Example 1; The binder includes sodium carboxymethyl cellulose and polyvinylidene fluoride in a weight ratio of 1.8:1, wherein the sodium carboxymethyl cellulose is 5.14 g and the polyvinylidene fluoride is 2.86 g; The conductive agent is graphene.

[0041] Example 3 A method for preparing a positive electrode slurry composition for a sodium ion battery is different from that of Example 2 in that: the amount of the conductive agent used is 2 g, and the rest is the same as that of Example 2.

[0042] Example 4 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that the weight ratio of sodium carboxymethyl cellulose to polyvinylidene fluoride is 2.2:1, the sodium carboxymethyl cellulose is 4.125 g, and the polyvinylidene fluoride is 1.875 g, and the rest is the same as Example 2.

[0043] Example 5 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that the weight ratio of sodium carboxymethyl cellulose to polyvinylidene fluoride is 2:1, the sodium carboxymethyl cellulose is 4g, the polyvinylidene fluoride is 2g, and the rest is the same as Example 2.

[0044] Example 6 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that sodium nickel manganese oxide is prepared using sodium nickel manganese oxide prepared in Preparation Example 2, and the rest is the same as Example 2.

[0045] Example 7 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that: the conductive agent includes graphene and carbon nanotubes in a weight ratio of 1:1, the graphene is 1.25g, the carbon nanotubes are 1.25g, the carbon nanotubes are single-walled carbon nanotubes prepared in Preparation Example 3, and the rest are the same as Example 2.

[0046] Example 8 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that: the conductive agent includes graphene and carbon nanotubes in a weight ratio of 1:4, the graphene is 0.5g, the carbon nanotubes are 2g, wherein the carbon nanotubes are single-walled carbon nanotubes obtained in Preparation Example 4, and the rest are the same as Example 2.

[0047] Example 9 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that: the conductive agent includes graphene and carbon nanotubes in a weight ratio of 1:2, the graphene is 0.83g, the carbon nanotubes are 1.67g, wherein the carbon nanotubes are single-walled carbon nanotubes obtained in Preparation Example 3, and the rest are the same as Example 2.

[0048] Example 10 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 2 in that: the conductive agent includes graphene and carbon nanotubes in a weight ratio of 1:3, the graphene is 0.625g, the carbon nanotubes are 1.875g, wherein the carbon nanotubes are single-walled carbon nanotubes obtained in Preparation Example 3, and the rest are the same as Example 2.

[0049] Embodiment 11 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 10 in that the carbon nanotubes are single-walled carbon nanotubes prepared in Preparation Example 5, and the rest is the same as Example 10.

[0050] Example 12 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 10 in that the carbon nanotubes are single-walled carbon nanotubes prepared in Preparation Example 6, and the rest is the same as Example 10.

[0051] Example 13 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 10 in that the carbon nanotubes are single-walled carbon nanotubes prepared in Preparation Example 7, and the rest is the same as Example 10.

[0052] Embodiment 14 A method for preparing a positive electrode slurry composition for a sodium ion battery, which is different from Example 10 in that the carbon nanotubes are single-walled carbon nanotubes prepared in Preparation Example 8, and the rest is the same as Example 10.

[0053] Comparative Example 1 The difference from Example 2 is that the amount of the conductive agent used is 1 g, and the rest is the same as Example 2.

[0054] Comparative Example 2 The difference from Example 2 is that the amount of the conductive agent used is 4 g, and the rest is the same as Example 2.

[0055] Comparative Example 3 The difference from Example 2 is that only sodium carboxymethyl cellulose is used as the binder, and the amount of sodium carboxymethyl cellulose used is 6 g. The rest is the same as Example 2.

[0056] Comparative Example 4 The difference from Example 2 is that only polyvinylidene fluoride is used as the binder, and the amount of polyvinylidene fluoride used is 6 g. The rest is the same as Example 2.

[0057] Comparative Example 5 The difference from Example 2 is that the weight ratio of sodium carboxymethyl cellulose to polyvinylidene fluoride is 1:1, the sodium carboxymethyl cellulose is 3 g, and the polyvinylidene fluoride is 3 g. The rest is the same as Example 2.

[0058] Comparative Example 6 The difference from Example 2 is that the weight ratio of sodium carboxymethyl cellulose to polyvinylidene fluoride is 3:1, the sodium carboxymethyl cellulose is 4.5 g, and the polyvinylidene fluoride is 1.5 g. The rest is the same as Example 2.

[0059] Application Example 1-14 An application of a positive electrode slurry composition for a sodium ion battery, wherein the positive electrode slurry compositions prepared in Examples 1 to 14 are respectively spin-coated on a metal aluminum foil, dried at 110° C. for 12 h under vacuum conditions, and then compacted at a pressure of 16 MPa to obtain a positive electrode sheet; wherein the single-sided surface density of the positive electrode sheet is 9.75±0.1 mg / cm 2 , double-sided surface density is 19.50±0.2mg / cm 2 .

[0060] Comparative Application Examples 1-6 The difference from Application Example 2 is that the positive electrode slurry composition prepared in Comparative Examples 1-6 is used, and the rest is the same as Application Example 2.

[0061] Comparative Application Example 7 The difference from Application Example 2 is that spin coating is not used when coating the positive electrode slurry composition, and the rest is the same as Application Example 2.

[0062] Performance Testing With the metal sodium sheet as the negative electrode, the positive electrode sheet, the separator and the negative electrode sheet prepared in Application Examples 1-14 and Comparative Application Examples 1-7 were assembled into a sodium ion battery in a glove box filled with Ar gas in a certain order, and the sodium ion battery was naturally left at room temperature for 12 hours before the electrochemical performance test was carried out; wherein the electrolyte was 1 mol / L sodium perchlorate / fluoroethylene carbonate+propylene carbonate, and the volume ratio of sodium perchlorate / fluoroethylene carbonate to propylene carbonate was 5:95; the separator was pure glass fiber filter paper Whatman GFD (thickness 675 μm); ① Using the Xinwei test system, the prepared sodium ion battery was subjected to the first charge and discharge test at room temperature, a voltage range of 2.75V-4.2V, and a current density of 0.1C (1C = 180mA / g). The results are shown in Table 1; ② Using the Xinwei test system, the prepared sodium ion battery was cycled for 200 and 500 cycles at room temperature, a voltage range of 2.75V-4.2V, and a current density of 10C (1C = 180mA / g), and the capacity retention rate (%) was recorded. The results are shown in Table 1; ③ The rate performance of the prepared sodium ion battery was tested using the Xinwei test system at room temperature and a voltage range of 2.75V-4.2V. The current density gradient was set to 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, and finally back to 0.1C. The discharge specific capacity of the sodium ion battery at 10C was recorded to represent the rate performance of the sodium ion battery. The results are shown in Table 1.

[0063] Table 1 Performance test results Data Analysis: As can be seen from Table 1, the sodium ion battery prepared in Application Examples 1-5 of the present application has an initial charge and discharge specific capacity of more than 175 mAh / g at a current density of 0.1C, and a capacity retention rate of more than 70% after 200 cycles at a current density of 10C, and a capacity retention rate of more than 38% after 500 cycles, and a discharge specific capacity of more than 140 mAh / g at a current density of 10C, indicating that the positive electrode slurry composition of the present application can make the prepared sodium ion battery have good charge and discharge performance, strong cycle stability and high rate performance, and strong electrochemical performance. Among them, by comparing the data of Application Example 2 and Application Example 3, it can be found that when the amount of conductive agent used is further optimized, the electrochemical performance of the sodium ion battery can be further improved. By comparing the data of Application Example 2 and Application Examples 4-5, it can be found that when the ratio of sodium carboxymethyl cellulose and polyvinylidene fluoride is further optimized, the electrochemical performance of the sodium ion battery can be further improved.

[0064] The sodium ion battery prepared in Application Example 6 has an initial charge and discharge specific capacity at a current density of 0.1C that is smaller than that in Application Example 2. At a current density of 10C, the capacity retention rate after 200 and 500 cycles is smaller than that in Application Example 2. At a current density of 10C, the discharge specific capacity is smaller than that in Application Example 2, indicating that compared with the use of P3 phase sodium nickel manganese oxide, the present application further uses P6 phase sodium nickel manganese oxide, which can further improve the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0065] The sodium ion batteries prepared in Application Examples 7-14 have a first charge and discharge specific capacity at a current density of 0.1C that is greater than that in Application Example 2. At a current density of 10C, the capacity retention rate after 200 and 500 cycles is greater than that in Application Example 2. At a current density of 10C, the discharge specific capacity is greater than that in Application Example 2, indicating that the mixed use of graphene and carbon nanotubes in this application can give full play to the synergistic effect of each other, thereby improving the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0066] Among them, by comparing the data of application examples 7-10, it can be found that when the ratio of graphene and carbon nanotubes is further optimized, the charge and discharge performance, cycle stability and rate performance of the sodium ion battery can be further improved. By comparing the data of application example 10 and application examples 11-12, it can be found that the sodium ion battery prepared in application examples 11-12 has a first charge and discharge specific capacity at a current density of 0.1C less than that of application example 10, and at a current density of 10C, the capacity retention rate after 200 and 500 cycles is less than that of application example 10, and at a current density of 10C, the discharge specific capacity is less than that of application example 10, indicating that if the reaction temperature is too high when preparing single-walled carbon nanotubes, it will affect the conductivity of the single-walled carbon nanotubes, thereby reducing the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0067] By comparing the data of Application Example 10 and Application Example 13, it can be found that the initial charge and discharge specific capacity of the sodium ion battery prepared in Application Example 13 at a current density of 0.1C is smaller than that of Application Example 10. At a current density of 10C, the capacity retention rate after 200 and 500 cycles is smaller than that of Application Example 10. At a current density of 10C, the discharge specific capacity is smaller than that of Application Example 10, indicating that when preparing single-walled carbon nanotubes, first introducing hydrogen and then introducing methane will affect the conductivity of the single-walled carbon nanotubes, thereby reducing the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0068] By comparing the data of Application Example 10 and Application Example 14, it can be found that the sodium ion battery prepared in Application Example 14 has a smaller initial charge and discharge specific capacity at a current density of 0.1C than that in Application Example 10, and at a current density of 10C, the capacity retention rate after 200 and 500 cycles is smaller than that in Application Example 10, and at a current density of 10C, the discharge specific capacity is smaller than that in Application Example 10, indicating that compared with multi-walled carbon nanotubes, the single-walled carbon nanotubes used in this application can improve the charge and discharge performance, cycle stability and rate performance of sodium ion batteries.

[0069] Comparative Example 1-2 shows that the sodium ion battery prepared has a lower initial charge and discharge specific capacity than that of Application Example 2 at a current density of 0.1C. At a current density of 10C, the capacity retention rate after 200 and 500 cycles is lower than that of Application Example 2. Moreover, at a current density of 10C, the discharge specific capacity is also lower than that of Application Example 2, indicating that the present application further optimizes the amount of the conductive agent, which can improve the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0070] The sodium ion batteries prepared in comparative application examples 3-6 have lower initial charge and discharge specific capacities than those in application example 2 at a current density of 0.1C. At a current density of 10C, the capacity retention rates after 200 and 500 cycles are lower than those in application example 2. Moreover, at a current density of 10C, the discharge specific capacity is also lower than that in application example 2, indicating that the present application adopts a mixed combination of sodium carboxymethyl cellulose and polyvinylidene fluoride and controls the weight ratio of the two, which can enhance the stability of the bonding structure of the positive electrode slurry composition, thereby improving the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0071] The sodium ion battery prepared in comparative application example 7 has a lower initial charge and discharge specific capacity than that in application example 2 at a current density of 0.1C. At a current density of 10C, the capacity retention rate after 200 and 500 cycles is lower than that in application example 2. Moreover, at a current density of 10C, the discharge specific capacity is also lower than that in application example 2, indicating that the present application further adopts a method of rotary coating of the positive electrode slurry composition, which can improve the uniformity of the coating, thereby improving the charge and discharge performance, cycle stability and rate performance of the sodium ion battery.

[0072] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A sodium ion battery positive electrode slurry composition, characterized in that: The raw materials used include the following components: 100 parts by weight of sodium nickel manganate; Conductive agent 1.5-2.5 parts by weight; 6-8 parts by weight of binder; The binder comprises sodium carboxymethyl cellulose and polyvinylidene fluoride in a weight ratio of (1.8-2.2):1; The particle size D50 of the sodium nickel manganate is 6-10 μm, and the purity is greater than 99.5%.

2. A sodium ion battery positive electrode slurry composition according to claim 1, characterized in that: The amount of the conductive agent used is 2 parts by weight.

3. A sodium ion battery positive electrode slurry composition according to claim 1, characterized in that: The weight ratio of the sodium carboxymethyl cellulose to polyvinylidene fluoride is 2:

1.

4. A sodium ion battery positive electrode slurry composition according to claim 1, characterized in that: The sodium nickel manganese oxide is P6 phase sodium nickel manganese oxide.

5. The sodium ion battery positive electrode slurry composition according to claim 1, characterized in that: The conductive agent includes graphene and carbon nanotubes in a weight ratio of 1:(2-3).

6. A sodium ion battery positive electrode slurry composition according to claim 5, characterized in that: The weight ratio of the graphene to the carbon nanotubes is 1:

3.

7. A sodium ion battery positive electrode slurry composition according to claim 5, characterized in that: The carbon nanotubes are single-walled carbon nanotubes.

8. A sodium ion battery positive electrode slurry composition according to claim 7, characterized in that: The single-walled carbon nanotubes are prepared by the following method: At a temperature of 1000-1050° C. and under the protection of an inert gas, hydrogen and methane are simultaneously introduced into a system containing a catalyst for reaction for 25-35 minutes, and then cooled to room temperature to obtain single-walled carbon nanotubes.

9. A method for preparing the sodium ion battery positive electrode slurry composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: The sodium nickel manganese oxide, the conductive agent and the binder are mixed evenly, then dispersed in N-methylpyrrolidone, and wet ball milled to obtain a positive electrode slurry composition for a sodium ion battery.

10. An application of the sodium ion battery positive electrode slurry composition according to any one of claims 1 to 8, characterized in that: The sodium ion battery positive electrode slurry composition is coated on a substrate, dried, solidified and compacted to obtain a positive electrode sheet.

Citation Information

Patent Citations

  • Positive electrode and positive electrode paste with high energy density, and battery containing positive electrode

    CN105470517A

  • Aqueous slurry for positive electrode, positive electrode composition, lithium ion secondary battery comprising said positive electrode composition, and method for producing same

    CN114830378A

  • Sodium-ion battery positive active material and preparation method and application thereof

    CN116525810A

  • Preparation method of single-walled carbon nanotube conductive paste

    CN117163947A